Catalytic oxidative desulfurization of diesel fuel utilizing a polymolybdate alumina supported catalyst: characterization, catalytic activity and mechanistic study - Wan Abdullah, Wan Nazwanie (2015)
The performance of oxidative desulfurization of commercial diesel by alumina supported polymolybdate based catalyst system was studied using tert-butyl hydroperoxide (TBHP) as an oxidizing agent. Transition metals such as Fe, Co and Cu were introduced onto the surface of alumina, prior to the impregnation of MoO3. The results showed that the oxidation of sulfur in commercial diesel with TBHP decreased in the order: Fe/MoO3/Al2O3 > Co/MoO3/Al2O3 > Cu/MoO3/Al2O3. Further investigations on doped molybdenum revealed that Fe/MoO3/Al2O3, calcined at 500 °C was the best catalyst in this study. The catalyst was able to reduce sulfur levels in commercial diesel from 440 ppmw to less than 18 ppmw. In addition, 96 % of total sulfur was removed after a second extraction. Based on our results, the reaction mechanisms for oxidation of sulfur compound, in the presence of Fe/MoO3/Al2O3 catalyst, to the corresponding sulfones may be suggested.